The Usborne Internet-linked children's world cookbook - Wilkes, Angela (Usborne ; EDC, 2002)
Contains more than forty simple recipes from around the world and provides information on what is traditionally eaten in different countries and the ingredients which are used; includes addresses for Web sites which offer more coverage of the topic.